The Chinese "Open Class": a conceptual rendering and historical account. Issue 2 (3rd April 2018) - Wu, Huiping; Clarke, Anthony
Abstract: The intent of this paper is to make sense of and share with a broader community of teachers and teacher educators a professional development phenomenon that is peculiar to the Chinese elementary and secondary school context. This practice, known as the Open Class, has at least three forms: intra-school, inter-school, and competitive. These forms are defined and delineated at the outset of the paper with particular attention to the distinguishing characteristics of each. This conceptual groundwork paves the way for a detailed historical accounting of this phenomenon over the past 65 years. What we learn is that the Open Class, as a professional development strategy, has waxed and waned based on the political and educational emphases of the day but nonetheless is alive and well in modern-day China. Indeed, it is so commonplace that it has become a norm in Chinese schools. While there remains much to be learned about the Open Class, four lessons learned as a result of the exposition offered in this paper provide a strong basis and valuable springboard for further exploration.